2016
DOI: 10.2217/mmt-2016-0020
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Development of Intralesional Therapies for Melanoma

Abstract: Advances in immune therapy have changed the landscape of advanced melanoma treatment. Intralesional therapy is an important type of immune therapy due to its efficacy and safety, especially in the setting of locoregional metastases. These therapies induce frequent responses in injected lesions as well as distant nontreated lesions through a 'bystander' effect of priming an antitumor immune response. The culmination of nearly a century of innovation has led to the approval of the first US FDA approved intralesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…We demonstrated that the cytotoxic effect of 1 mM RB had few side effects on normal tissues, and this dose is consistent with that used to treat melanoma in clinical trials [ 40 ]. Several studies have shown that RB intralesional injection trigger iDCs to migrate into the tumour [ 41 , 42 ], although occasionally, the DCs are not able to enter the TME due to the immunosuppressive nature of the TME, which leads to the insufficient infiltration of effective immune cells into the TME [ 34 ]. Therefore, the intralesional injection of both RB and iDCs could subvert these immunosuppressive effects and guarantee sufficient antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the cytotoxic effect of 1 mM RB had few side effects on normal tissues, and this dose is consistent with that used to treat melanoma in clinical trials [ 40 ]. Several studies have shown that RB intralesional injection trigger iDCs to migrate into the tumour [ 41 , 42 ], although occasionally, the DCs are not able to enter the TME due to the immunosuppressive nature of the TME, which leads to the insufficient infiltration of effective immune cells into the TME [ 34 ]. Therefore, the intralesional injection of both RB and iDCs could subvert these immunosuppressive effects and guarantee sufficient antigen presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from this, other IL therapies including PV-10 (Rose Bengal), IL-12 plasmid electroporation, and Coxsackievirus A21 have shown favorable clinical outcomes. [ 60 ]…”
Section: P Ros a Ssociated With T Reatment Of Il A Gentsmentioning
confidence: 99%
“…The survival of patients with unresectable and metastatic melanoma has substantially improved over the last decade with the development of novel systemic immunotherapies, such as anti-CTLA-4 and anti-PD-1/anti-PD-L1 agents and targeted therapies [2]. Beyond systemic treatment, intratumoral therapies may benefit specific patient groups, for example, those with extensive and recurrent locoregional disease and high tumor burden [3]. Due to a relatively lower risk for toxicity, intratumoral therapies might be a valuable option in elderly patients with co-morbidities, where systemic treatment options are contraindicated [4].…”
mentioning
confidence: 99%